Online Sexual Activities and Sexual Identity Development - Sipes, Jessica (Curtin University, 2020)
Sexual identity can be explored and developed in online and offline contexts. Over three studies this thesis looked at how people define sexual identity, associations between online and offline sexual activities and sexual identity development, and associations between online sexual activities, sexual identity, and sexual wellbeing and communication. These findings suggest people use the internet to learn about sexual identity and they highlight the importance of educating people on assessing online sources of information.